Dominant RP in the Middle While Recessive in Both the N- and C-Terminals Due to RP1 Truncations: Confirmation, Refinement, and Questions - Wang, Junwen; Xiao, Xueshan; Li, Shiqiang; Wang, Panfeng; Sun, Wenmin; Zhang, Qingjiong (Frontiers in Cell and Developmental Biology, 2021)
RP1 truncation variants, including frameshift, nonsense, and splicing, are a common cause of retinitis pigmentosa (RP). RP1 is a unique gene where truncations cause either autosomal dominant RP (adRP) or autosomal recessive RP (arRP) depending on the location of the variants. This study aims to clarify the boundaries between adRP and arRP caused by RP1 truncation variants based on a systemic analysis of 165 RP1 variants from our in-house exome-sequencing data of 7,092 individuals as well as a thorough review of 185 RP1 variants from published literature. In our cohort, potential pathogenic variants were detected in 16 families, including 11 new and five previously described families. Of the 16, seven families with adRP had heterozygous truncations in the middle portion, while nine families with either arRP (eight) or macular degeneration had biallelic variants in the N- and C-terminals, involving 10 known and seven novel variants. In the literature, 147 truncations in RP1 were reported to be responsible for either arRP (85) or adRP (58) or both (four). An overall evaluation of RP1 causative variants suggested three separate regions, i.e., the N-terminal from c.1 (p.1) to c.1837 (p.613), the middle portion from c.1981 (p.661) to c.2749 (p.917), and the C-terminal from c.2816 (p.939) to c.6471 (p.2157), where truncations in the middle portion were associated with adRP, while those in the N- and C-terminals were responsible for arRP. Heterozygous truncations alone in the N- and C- terminals were unlikely pathogenic. However, conflict reports with reverse situation were present for 13 variants, suggesting a complicated pathogenicity awaiting to be further elucidated. In addition, pathogenicity for homozygous truncations around c.5797 and thereafter might also need to be further clarified, so as for missense variants and for truncations located in the two gaps. Our data not only confirmed and refined the boundaries between dominant and recessive RP1 truncations but also revealed unsolved questions valuable for further investigation. These findings remind us that great care is needed in interpreting the results of RP1 variants in clinical gene testing as well as similar features may also be present in some other genes.